Community empowerment through waste processing innovation based on maggot cultivation - Adi Santoso; Ardyan Firdausi Mustoffa; Dwi Astuti; Riawan Riawan (Universitas Muhammadiyah Magelang, 2024)
The low public awareness of the importance of waste management has an impact on increasing the volume of waste, especially organic waste. This community service activity aims to improve the knowledge and skills of the Turi Village community in managing organic waste through the cultivation of economically valuable maggots. The implementation method includes socialization, training, and direct assistance. The results of this activity show a significant increase in community knowledge and skills in managing organic waste. In addition, this activity has also succeeded in changing community behavior in managing household waste. Thus, this community service activity not only provides solutions to waste problems, but also contributes to improving community welfare and environmental preservation.